MENGENAL RITME SIKARDIAN DAN PENTINGNYA MANAJEMEN TIDUR BAGI TARUNA AKADEMI MILITER - Marwita, Paulin (PPM Sdirjianbang Akademi Militer, 2024)
Sleep is a routine thing that every living creature does every day, it is called a circadian rhythm, which make us forget about its benefits and its dangers if it’s disturbed. Management of Sleep is essential for soldiers and cadets for military training and mission operations. Health cicardian rhythm will maintain health, increase performance and academic achievement. On the contrary, its disruption will cause diseases, decrease performance and academic achievement and induce fatal working accident or death. Unfortunately, sleep deficits is common in military personnel and recruits such cadets in US Military Academy. Friction often exists between meeting mission requirements and obtaining adequate sleep or rest in an operational environment, therefore management of sleep important to maintain health, sustainability service member and survival of its unit. Health circadian rhythm will produce less morbidity and mortality also avoid unnecessary degradation national military defense. It is recommended for military officers and cadets to understand the circadian rhythm in order to practice it for himself and his unit and to educate men under his command to succeed of military training exercises and mission operations and mitigating the catastrophic degradation of national defense due to disruption of the Circadian Rhythm.